The Equal-Sacrifice Social Welfare Function with an Application to Optimal Income Taxation - Kristoffer Berg; Paolo Giovanni Piacquadio (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We propose and axiomatically characterize a family of welfare criteria that prioritize individuals making larger sacrifices. By combining efficiency with a concern for equality of sacrifice, our criteria avoid serious shortcomings of utilitarianism. We illustrate our results within the Mirrleesian optimal taxation framework. Our simulated equal-sacrifice optimal tax schedule for the US has marginal tax rates in line with the US tax system and about 20 percentage points lower than the utilitarian recommendation.
Keywords: D63; H21; I31; 330; equal-sacrifice principle; optimal income taxation; welfare criterion